2019
DOI: 10.1080/17453674.2019.1644069
|View full text |Cite
|
Sign up to set email alerts
|

General anesthesia might be associated with early periprosthetic joint infection: an observational study of 3,909 arthroplasties

Abstract: Background and purpose — Periprosthetic joint infection (PJI) remains a devastating complication following total knee or total hip arthroplasty (TKA/THA). Nowadays, many studies focus on preventive strategies regarding PJI; however, the potential role of anesthesia in the development of PJI remains unclear.Patients and methods — All consecutive patients undergoing elective primary unilateral TKA or THA from January 2014 through December 2017 were included. Exclusion criteria included femoral fractures as the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Penalized Lasso regression identified male sex, higher BMI, higher ASA class, and general anesthesia as the most important factors increasing the risk of periprosthetic joint infection. Notably, all of these factors have also been previously reported as risk factors for periprosthetic joint infection 27 - 29 . Although previous analyses have also suggested that comorbid conditions may increase the risk of periprosthetic joint infection 30 , we did not include them because of the unavailability of the comorbidity data.…”
Section: Discussionmentioning
confidence: 89%
“…Penalized Lasso regression identified male sex, higher BMI, higher ASA class, and general anesthesia as the most important factors increasing the risk of periprosthetic joint infection. Notably, all of these factors have also been previously reported as risk factors for periprosthetic joint infection 27 - 29 . Although previous analyses have also suggested that comorbid conditions may increase the risk of periprosthetic joint infection 30 , we did not include them because of the unavailability of the comorbidity data.…”
Section: Discussionmentioning
confidence: 89%
“…This inflammatory response may also lead to acute cardiac injury and myocarditis as well as thromboembolic disease and disseminated intravascular coagulation 53,54 . Surgery may act as a promotor of these pathways by contributing to the pro‐inflammatory state, 55,56 while also causing additional strain on the heart and lungs 57–59 …”
Section: Discussionmentioning
confidence: 99%
“…[50][51][52] This inflammatory response may also lead to acute cardiac injury and myocarditis as well as thromboembolic disease and disseminated intravascular coagulation. 53,54 Surgery may act as a promotor of these pathways by contributing to the proinflammatory state, 55,56 while also causing additional strain on the heart and lungs. [57][58][59] The magnitude of the increased risk that a COVID-19 coinfection poses in the perioperative period mandates the development of strategies aimed at minimizing the risk of surgery to patients during the COVID-19 pandemic both at the individual and at a system level.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of insulin was then compared with other potential predictors of positive clinical cultures in all patients without diabetes. Insulin usage had a larger effect on reducing positive cultures than the avoidance of general anesthesia (Table VI), which has been associated with infections after joint surgery 13 , 14 .…”
Section: Resultsmentioning
confidence: 99%